So... Where Is Resilience? A Conceptual Reflection - Kalawski, Juan Pablo; Haz, Ana María (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
After critically reviewing the historical development of the concept of resilience in psychology and psychiatry, we propose not to consider resilience as a psychological variable in itself. Rather, we suggest that all persons who present an unexpected outcome in face of a given adverse situation should be considered resilient, regardless of the causes of that outcome. We further propose a distinction among protective factors, recovery factors, and behavioral control factors. Finally, implications of these ideas for research are discussed.